Sistem Informasi Geografis Pemetaan Persebaran Perceraian Faktor Ekonomi dan Pertengkaran di Kota Surakarta Tahun 2020-2023 - Dimas Aditya Saputra; Bambang Agus Herlambang; Ahmad Khoirul Anam (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
This study aims to utilize QGIS as a spatial analysis tool to map the distribution of divorces based on economic factors and disputes in Surakarta City during the 2020–2023 period. The data used includes spatial data in the form of Surakarta City's administrative map in shapefile format and non-spatial data comprising the number of divorces obtained from BPS Surakarta. Non-spatial data were integrated into spatial data using the "join attribute" feature in QGIS. The analysis process was conducted using classification methods to identify areas with the highest divorce density. The findings reveal that divorces due to economic factors are concentrated in low-income areas, such as Banjarsari and Jebres, while divorces caused by disputes exhibit a more evenly distributed pattern. The thematic maps were then exported into GeoJSON format for implementation on an interactive website accessible to the public and policymakers. This study contributes to the utilization of GIS technology in supporting data-driven decision-making.